Desenvolvimento do pensamento algébrico de professores dos anos iniciais em atividade de ensino: o pensamento teórico mediado por conceitos algébricos - Santos, Fernanda Cristina Ferreira [UNIFESP] (2020)
This research has investigated, in the context of teachers continuing mathematics education in the early years of elementary school, the theoretical thinking development mediated by algebraic concepts, that we understand to converge with algebraic thinking. The theoretical foundation has focused on the Historical-Cultural Theory, especially the contributions by Vigotski, Activity Theory, proposed by Leontiev, and Developmental Theory, by Davidov. With the intention of, in this development process of thinking, follow the phenomenon in motion, we chose to use the dialectical historical materialist investigative method, and in the experimental part, with a view to the production and collection of data, we used a formative experiment that took place in a public school in Guarulhos, through an extension action whose target audience was teachers who work in the early years of elementary school. For the organization of this formative experiment, we take the Teaching Orientation Activity as a theoretical and methodological proposal, proposing triggering situations for learning algebra that consider its historical and logical movement, in addition to stimulating the collective development of these proposals. Based on theoretical research and data analysis, we concluded that the development process of algebraic thinking was constituted by the approximation of conceptual nexus and the essence of algebra, wich allowed teachers, in teaching activities, to establish relations and general rules that could be manifested in particular cases, based on algebraic generalization. This process allowed an ascension movement in thought, from abstract to concrete, that led teachers to develop a more elaborate type of thinking, theoretical thought, relying on the mediation of algebraic concepts, that is, thinking algebraically. In this sense, there were indications of overcoming empirical thinking and changes in their personal senses around algebra and the organization of teaching aimed at the development of algebraic thinking in the early years of elementary school.